"Capping" out oxygen interference: An approach to achieve efficient hydrogen storage via Kubas binding. (20th April 2016) - Ahmad, Rafia; Bora, Pankaj Lochan; Singh, Abhishek Kumar
Abstract: Hydrogen bound via Kubas interaction on metal decorated light weight materials forebodes a much efficient alternative for the fast depleting fossil fuels. However, oxygen interference in hydrogen storage on metal decorated carbonaceous systems obstructs the successful realization of the theoretically promised high storage of Kubas bound H2 . The interference is a consequence of preferred O2 binding at the metal site, thereby blocking it for H2 adsorption. Here, we report that arene capping of a Sc-metallacarborane (MCB) efficiently reverses the preferential adsorption of O2 over H2 . The capped MCB completely repels O2 off the Sc-site allowing purely Kubas binding of H2 . This is enabled by the down-shift of the d -band center of Sc below the Fermi-level from 1.29 eV in the uncapped to 5.67 eV in the capped MCB, respectively. The optimised d -band center position enables the empty Sc antibonding states to only be available for hydrogen adsorption via Kubas interaction, thereby, to completely avoid oxygen binding. This novel approach tunes a cluster electronically to enhance gas adsorption selectivity, which can be efficiently ulitized in various catalytic, sensing and gas storage systems. Highlights: Oxygen interference completely eliminated by arene capping. Optimised d-band center of Sc by arene capping prevents oxygen adsorption. Complete hydrogen coverage observed at room temperature and 200 bar H2 partial pressure. Arene capped Sc-MCB adsorbs and desorbs 7 dihydrogens at ambient conditions. The capping concept is generalized on systems with open metal sites for hydrogen storage.